Klasterisasi Desa Wisata Berbasis Ketahanan Bencana dan Masyarakat di Desa Kunjir, Lampung Selatan - Rusmiati, Fadhilah; Persada, Citra; Hardilla, Dini (Universitas muhammadiyah palembang, 2023)
Kunjir Village has been designated as a Leading Tourism Village by the South Lampung Regency Government in early 2022. However, Kunjir Village is still have declining in tourism activities, especially after tsunami disaster in 2018. Based on this potential disaster, the authors in previous research have formulate into 4 (four) zoning of Kunjir Village’s coastal area. These zoning directives needs to be completed by actual data based on the potential for new tourism development and the aspirations of the community. The purpose of this study is to arrange clustering of tourist villages based on regional spatial conditions by considering environmental conditions in order to support people's welfare. This research is a descriptive study using qualitative methods with secondary data sources and information from respondents selected by purposive sampling with conducting structured interviews. The analysis was carried out by combining this research findings with the previous research results. The results of this study are developt 4 (four) superior tourism clusters including the Kunjir's Giant Seawall Cluster, the Kunjir Culinary Tour Cluster, the Kunjir Hot Springs and Waterfall Cluster, and the Kunjir Open Air Museum Cluster. This tourism village clustering can be used as a reference and will be able to be held regularly then become the tourism agenda of South Lampung Regency.